PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT INDO BATAM EKATAMA - Fernando, Fernando; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
This study aims to evaluate the impact on employee performance in PT Indo Batam Ekatama of workload, work environment and training. This method of analysis uses techniques of quantitative research. The knowledge collection approach is to distribute questionnaires to 107 respondents. Validity, reliability, normality, multicollinearity, heterokedastisitas, multiple linear regression analysis, t test and F test were used to analyze the results. Coefficient of determination Adjusted R Square indicate that the workload, work environment and training variable have an effect of 0.00 percent influence on employee performance variable. The findings of this study show that partly workload has an effect on employee performance, considering significant value 0.001 lower than α value 0.05 and t value 3.417 higher than t table 1.982 (H1 accepted), work environment has impact on employee performance because its significant value 0.000 lower than α value 0.05 and t value 5.136 higher than t table 1.982 (H2 accepted), training affects employee performance because its significant value is 0.007 lower than α value 0.05 and t value 2.763 higher than t table 1.982 (H3 accepted), while the workload, work environment and training have a significant impact on employee performance at the same time because its significant value 0.000 lower than α value 0.05 and f value 62.217 higher than f table 3.08 (H4 accepted).